Bystanders’ attitudes towards drone delivered Automated External Defibrillators for out-of-hospital cardiac arrest: A qualitative interview study - Celia J. Bernstein; Christopher M. Smith; Carl Powell; Mary O’Sullivan; Mark Holt; Keith Couper; Nigel Rees (PLoS ONE, 2025)
Background Early cardiopulmonary resuscitation (CPR) and defibrillation with Automated External Defibrillators (AEDs) by the public at an out-of-hospital cardiac arrest (OHCA) increases patient survival, but AEDs are infrequently used. Using drones to deliver AEDs may be one way to increase uptake, but there is limited understanding about what members of the public think about this. The aim of the study was to explore public attitudes towards drone AED delivery for OHCA. Methods We conducted 14 remote, semi-structured interviews with real-life OHCA bystanders. Participants were recruited via social media, a UK cardiac arrest survivor charity and the Welsh Ambulance Services University NHS Trust. We analysed data using the Theoretical Domains Framework and mapped findings to the Capability, Opportunity and Motivation model of Behaviour (COM-B) to identify perceived barriers and facilitators to the retrieval and use of drone-delivered AEDs. We used The Behaviour Change Wheel to identify potential interventions to optimise use of drone-delivered AEDs. Results Participants experienced varying levels of physical and social opportunities in relation to (un)available AEDs and (in)appropriate support from the call-handler, affecting the likelihood of them performing CPR and/or using an AED effectively. Most participants were unsure about how to use an AED, and none knew how a drone-delivered AED system would work in practice. Many participants questioned whether they would possess sufficient capability and motivation to retrieve and/or operate a drone-delivered AED during a time-critical emergency. There were five key themes for potential interventions: incorporating information about drone-delivered AED use into pre-existing training programmes and materials; ensuring drone use complies with specific regulatory and/or legislative requirements; making the drone-delivered AED easy to identify and access; optimising call-handler scripts to incorporate drone-delivered AED use; providing social support via a robust co-responder model to complement drone-delivered AED use. Conclusions Participants accepted drone-delivered AEDs for OHCA, but were unsure if it would be effective. They identified several issues that we addressed through the development of a comprehensive intervention framework. A comprehensive call-handler script that incorporates drone-delivered AED use and support for bystanders was the most salient potential intervention for future testing by relevant stakeholders.